Optimization of submarine submersible search and rescue path based on simulated annealing - Yue, Yujun; Dong, Xingqi (Transactions on Computer Science and Intelligent Systems Research, 2024)
The aim of this paper is to apply models and algorithms to address the problem of searching and rescuing lost underwater vehicles. This paper main work is divided into three steps: establishing a geographic model, establishing a simulation model, and optimizing the search model. A model is built to predict the drift path of underwater vehicles in the ocean, and an optimization search model based on simulated annealing algorithm is used to find the optimal search and rescue strategy to locate the underwater vehicle in the shortest time possible. Experimental results demonstrate that by utilizing simulated annealing iterations and spatial physics analysis methods, it is possible to predict the path of underwater vehicles and identify the optimal search points, thereby improving rescue efficiency and rapidly locating the lost underwater vehicle.